Ensemble NASNet Deep Feature Generator Based Underwater Acoustic Classification Model - Yaman, Orhan; Tuncer, Türker (Murat GÖK, 2021)
Sualtı akustiği, gelişmiş sinyal işleme için önemli ve karmaşık araştırma alanlarından biridir. Bu çalışmada, su altı araçlarının yön tespiti için derin öğrenme ve makine öğrenmesi tabanlı bir yöntem önerilmiştir. Sualtı robotu kullanılarak yeni bir veri seti toplandı. Veri setini oluşturmak için su altına bir mikrofon yerleştirildi. Su altında hareket eden Uzaktan Kumandalı Sualtı Aracının (ROV) pervanelerinin sesleri toplandı. Önce su altında hareketsiz bir ses kaydı yapıldı. Sualtı robotu x, y ve z eksenleri boyunca hareket etti ve bir ses veri seti oluşturuldu. Bu veri seti toplamda dört sınıftan oluşmaktadır. Bu sesler üzerinde özellik çıkarımı için NASNetLarge ve NASNetMobile derin öğrenme modelleri uygulanmıştır. Bu iki derin öğrenme modelinin özellikleri birleştirilmiştir. Elde edilen öznitelikler arasından en ağırlıklı öznitelikleri seçmek için chi2 yöntemi kullanılmıştır. Ardından, seçilen özellikleri sınıflandırmak için Destek Vektör Makinesi (SVM) algoritması kullanılır. Sınıflandırmada Doğrusal SVM algoritması ile %77,66 doğruluk hesaplanmıştır.

Underwater acoustics is one of the important and complex research areas for advanced signal processing. In this study, a deep learning and machine learning-based method are proposed for direction detection of underwater vehicles. A new dataset was collected using the underwater robot. A microphone was placed underwater to create the dataset. The sounds of the propellers of the Remotely Operated Underwater Vehicle (ROV) moving underwater were collected. First, a still sound recording was made underwater. The underwater robot moved along the x, y, and z axes, and a sound dataset was created. This data set consists of four classes in total. NASNetLarge and NASNetMobile deep learning models have been applied for feature extraction on these sounds. The features of these two deep learning models are combined. The chi2 method was used to select the most weighted features among the obtained features. Then, the Support Vector Machine (SVM) algorithm is used to classify the selected features. In classification, 77.66% accuracy was calculated with the Linear SVM algorithm.
Ensemble NASNet Deep Feature Generator Based Underwater Acoustic Classification Model
Keywords: Engineering; Mühendislik